Human Rights-Based Correctional Rehabilitation in Juvenile Development: An Empirical Study of the Implementation of Law No. 22 of 2022 in Banda Aceh - Awaluddin Awaluddin; Siti Rahmah; Fazzan Fazzan; Dede Suhendra; Muhammad Nur; Cut Megawati (Yayasan Abdurrauf Cendekia Nusantara, 2026)
This study examines the implementation of Law Number 22 of 2022 on Corrections in the development of juvenile inmates at LPKA Class II Banda Aceh, which still reveals a gap between legal norms and empirical practices. The objective of this research is to analyze the effectiveness of a human rights–based correctional approach in enhancing the personality and independence of juvenile inmates. This study employs a descriptive qualitative method with an empirical approach, utilizing primary data obtained through in-depth interviews and observations, as well as secondary data derived from relevant literature and official documents. The findings indicate that the fulfillment of fundamental rights, such as education, healthcare, spiritual guidance, and vocational training, significantly contributes to positive transformations in mindset, attitudes, and behavior. Furthermore, cross-sectoral collaboration strengthens the effectiveness of rehabilitation programs. However, implementation remains constrained by limited resources and external social factors. This study concludes that a human rights–based approach is effective in supporting juvenile rehabilitation, yet requires institutional strengthening, capacity building, and sustained inter-agency collaboration. [Penelitian ini mengkaji implementasi Undang-Undang Nomor 22 Tahun 2022 tentang Pemasyarakatan dalam pembinaan narapidana anak di LPKA Kelas II Banda Aceh, yang masih menunjukkan adanya kesenjangan antara norma hukum dan praktik empiris. Tujuan penelitian ini adalah menganalisis efektivitas pendekatan pemasyarakatan berbasis hak asasi manusia dalam meningkatkan kepribadian dan kemandirian narapidana anak. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan empiris, memanfaatkan data primer yang diperoleh melalui wawancara mendalam dan observasi, serta data sekunder yang diambil dari literatur dan dokumen resmi yang relevan. Temuan menunjukkan bahwa pemenuhan hak-hak dasar, seperti pendidikan, layanan kesehatan, bimbingan rohani, dan pelatihan kejuruan, berkontribusi signifikan terhadap transformasi positif dalam pola pikir, sikap, dan perilaku. Selain itu, kolaborasi lintas sektor memperkuat efektivitas program rehabilitasi. Namun, implementasi masih terkendala oleh keterbatasan sumber daya dan faktor sosial eksternal. Penelitian ini menyimpulkan bahwa pendekatan berbasis hak asasi manusia efektif dalam mendukung rehabilitasi remaja, namun memerlukan penguatan kelembagaan, pengembangan kapasitas, dan kolaborasi antarlembaga yang berkelanjutan.]